2013
DOI: 10.1371/journal.pone.0076552
|View full text |Cite
|
Sign up to set email alerts
|

What Patient Factors Predict Physicians’ Decision Not to Treat Latent Tuberculosis Infection in Tuberculosis Contacts?

Abstract: ObjectiveThe study aimed to determine factors that are associated with physicians’ decision to offer treatment for latent tuberculosis infection (LTBI) in contacts of patients with tuberculosis.MethodsWe performed a nested case-control study in a cohort of contacts of patients with pulmonary tuberculosis who had a tuberculin skin test (TST) ≥ 10 mm. Cases were those who were offered treatment for LTBI. Controls were randomly selected from those who were not offered treatment for LTBI by the reviewing physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…However, almost half of the contacts diagnosed with LTBI did not start on preventive treatment. A study conducted in Sydney, Australia, by DOBLER et al [16] showed that physicians' decisions to offer LTBI treatment may be correlated with factors associated with an increased risk of developing tuberculosis, such as young age and being a close contact of an index case. Unfortunately we were not able to determine whether these contact factors influenced physicians' decisions on treatment or whether patients' refusal was associated with starting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost half of the contacts diagnosed with LTBI did not start on preventive treatment. A study conducted in Sydney, Australia, by DOBLER et al [16] showed that physicians' decisions to offer LTBI treatment may be correlated with factors associated with an increased risk of developing tuberculosis, such as young age and being a close contact of an index case. Unfortunately we were not able to determine whether these contact factors influenced physicians' decisions on treatment or whether patients' refusal was associated with starting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Potential barriers to the uptake of LTBI testing and treatment include reluctance of providers to prescribe LTBI treatment (for example because of fear of facilitating the development of drug resistance with monotherapy, 99 or because the health providers are not convinced that the benefits of LTBI treatment outweigh the potential risk from adverse effects 100,101 ), reluctance of people with LTBI to undergo a prolonged course of treatment for an asymptomatic condition that may never progress to active TB disease, lack of trained and experienced medical staff, and lack of availability of single drugs in some low-and middle-income countries in which only combination therapy for treatment of active TB is readily available.…”
Section: Addressing the Barriers To Ltbi Screeningmentioning
confidence: 99%
“…Physicians may not prescribe evidence-based preventive treatments because they are more afraid of the risk of potential adverse effects from treatments than the higher risks of morbidity and mortality associated with the disease (eg, preventive tuberculosis treatment in patients with latent infection,4 anticoagulation for atrial fibrillation in high-risk patients5).…”
Section: Examples Of Cognitive Biases In Clinical Decision-makingmentioning
confidence: 99%